Structural and functional cardiac parameters across occupations: a cross-sectional study in differing work environments - Roman Leischik; Peter Foshag; Chayakrit Krittanawong; Ulrich Jehn; Richard Vollenberg; Markus Strauss (Scientific Reports, 2024)
Abstract Previous investigations have highlighted notable variations in cardiovascular risk indicators associated with various professional categories. However, only a few studies have examined structural and functional cardiac parameters using echocardiography within distinct occupational groups. Hence, this study endeavored to assess cardiac structural and functional parameters in three additional occupations: firefighters (FFs), police officers (POs), and office workers (OWs). This prospective study encompassed 197 male participants (97 FFs, 54 POs, and 46 OWs) from Germany. All participants underwent 2D and Doppler echocardiography in resting conditions; standard parasternal and apical axis views were employed to evaluate structural (diastolic and systolic) and functional (systolic and diastolic function, and strain) cardiac parameters. All three occupational groups exhibited a tendency towards septal hypertrophy. Notably, OWs exhibited the largest diastolic interventricular septum diameter (IVSd), at 1.33 ± 0.25 cm. IVSd significantly varied between POs and OWs (p = 0.000) and between POs and FFs (p = 0.025). Additionally, during diastole a substantially larger left ventricular posterior wall diameter (LVPWd) was observed in OWs compared to FFs (p = 0.001) and POs (p = 0.013). The left ventricular diastolic cavity diameter (LVIDd) and the left ventricular systolic cavity diameter (LVIDs) were significantly higher in POs than they were in FFs (LVIDd: p = 0.001; LVIDs: p = 0.009), and the LVIDd was notably higher in FFs (p = 0.015) and POs compared to OWs (p = 0.000). FFs exhibited significantly better diastolic function, indicated by higher diastolic peak velocity ratios (MV E/A ratio) and E/E’ ratios, compared to POs (E/A ratio: p = 0.025; E/E’ ratio: p = 0.014). No significant difference in diastolic performance was found between OWs and FFs. Significantly higher E’(lateral) values were noted in POs compared to FFs (p = 0.003) and OWs (p = 0.004). Ejection fraction did not significantly differ among FFs, POs, and OWs (p > 0.6). The left ventricular mass (LV Mass) was notably higher in POs than it was in FFs (p = 0.039) and OWs (p = 0.033). Strain parameter differences were notably improved in two- (p = 0.006) and four-chamber (p = 0.018) views for FFs compared to POs. Concentric remodeling was the predominant change observed in all three occupational groups. Significant differences in the presence of various forms of hypertrophy were observed in FFs, POs, and OWs (exact Fisher test p-values: FFs vs. OWs = 0.021, POs vs. OWs = 0.002). OWs demonstrated notably higher rates of concentric remodeling than FFs did (71.77% vs. 47.9%). This study underscores disparities in both functional and structural parameters in diverse occupational groups. Larger prospective studies are warranted to investigate and delineate differences in structural and functional cardiac parameters across occupational groups, and to discern their associated effects and risks on the cardiovascular health of these distinct professional cohorts.